Beelden 1983. - Hefting, Paul; Oosterhof, Gosse; van der Geer, Cees (Rotterdam : Rotterdamse Kunststichting, 1983)
Ahearn, John ; Allington, Edward ; Blacker, Kate ; O'Brien, Robert ; Calaway, Loren ; Cragg, Tony (Anthony) ; Genzken, Isa ; Houshiary, Shirazeh ; Kapoor, Anish ; Keister, Steve ; Kemps, Niek ; Lavier, Bertrand ; Mach, David ; Mark, Arno Van der ; Opie, Julian ; van der Pennen, Hans ; Rohling, Gerd ; Roothaan, Steef ; Saytour, Patrick ; Scolavino, Quintino ; Spalletti, Ettore ; Stoltz, David ; Teusch, Dieter ; Thomas, Kathleen ; Veneman, Peer ; Vermeiren, Didier ; Vilmouth, Jean-Luc ; Visch, Henk ; Vlugt, Harald ; Mantje, Aldert ; Woodrow, Bill
biog.
Nederlands & Engels
BeeldenSculpture 1983, Lijnbaancentrum, Galerie 't Venster, Westersingel 8, Galerie "Black Cat" en het Centrum Beeldende Kunst te Rotterdam, 13/5 - 22/6/1983. Rotterdamse Kunststichting, Rotterdam
boek
Keywords: Engeland; Frankrijk; Nederland; U.S.A.